The T.S. Eliot studies annual. (Clemson University Press, 2018)
The T.S. Eliot Studies Annual strives to be the leading venue for the critical reassessment of Eliot's life and work in light of the ongoing publication of his letters, critical volumes of his complete prose, the new edition of his complete poems, and the forthcoming critical edition of his plays. All critical approaches are welcome, as are essays pertaining to any aspect of Eliot's work as a poet, critic, playwright, editor, or foremost exemplar of literary modernism. John D. Morgenstern, General Editor Editorial Advisory Board: Ronald Bush, University of Oxford David E. Chinitz, Loyola University Chicago Anthony Cuda, University of North Carolina-Greensboro Robert Crawford, University of St Andrews Frances Dickey, University of Missouri John Haffenden, University of Sheffield Benjamin G. Lockerd, Grand Valley State University Gail McDonald, Goldsmiths, University of London Gabrielle McIntire, Queen's University Jahan Ramazani, University of Virginia Christopher Ricks, Boston University Ronald Schuchard, Emory University Vincent Sherry, Washington University at St. Louis.